Tradisi Pemanggilan Totem di Negeri Hutumuri: Kajian Antropologi Fungsionalisme dan Teologi Kontekstual - Resa Dandirwalu (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2021)
This article aims to analyze the Christian function and response toward the tradition of summoning the Totem (Upu) prior to the traditional rite in the Baileo of the community of Hutumuri Village. This study applies a qualitative research method which emphasizes the functions that emerge from problems in the community, and they were responded with contextual theology. The data used as the materials for analysis are obtained through interviews with the king and the traditional leaders in Hutumuri Village. The findings of this study indicate that the tradition of summoning the Totem, which is perpetually practiced by the community of Hutumuri village, is closely connected with several functions in the community’s life, such as the function of Soa identity, kinship, and morals. These functions are responded in Christian perspective such as contextual theology, so they bear the transformation, i.e., the functions of social identity and kinship have become the symbol of God’s Kingdom, and the moral function has turned to a creation-oriented spirituality. Thus, the tradition of summoning the Totem in the community of Hutumuri village is a culture that continues to be preserved as it has cultural and religious functions, which are valuable to promote harmony and balance in the community of Hutumuri village.